CO2 adsorption of bagasse waste feedstock using thermogravimetric analyses - Peres, Christiano Bruneli [UNESP]; Rosa, André Henrique [UNESP]; de Morais, Leandro Cardoso [UNESP] (Springer Nature, 2021)
Nowadays, global warming is mainly caused by increase in CO2 concentration in the environment; to mitigate this problem, an attractive strategy for efficient CO2 emission reduction was applied: carbon capture. Therefore, this work had as main objective to measure the capture of CO2, through two carbonaceous materials produced from sugar cane bagasse; this biochar was activated chemically with KOH, by two different processes: the impregnated biochar (CA-1) was taken to pyrolysis process at 350 °C and another sugarcane bagasse sample was also impregnated, but directly in dry biomass (CA-2), obtaining two carbonaceous material (CA-1 and CA-2), respectively. The prepared carbons were characterized by thermal analysis with heating rate of 10 °C min−1 in N2 atmosphere, showing two main stages: the first one close to 150 °C for biochar samples and the second one in the range of 150–600 °C for the same biochar samples, X-ray diffraction (XRD, peaks at 2θ = 28.41°; 40.50°; 44.52°; 50.29° and 58.61° for CA-1 and 2θ = 28.27°; 40.45°; 44.60°; 50.15° and 58.63° for CA-2), scanning electron microscopy (SEM) with energy-dispersive X-ray (EDX) and Fourier transform infrared spectroscopy (FTIR, showing peaks at 3675, 2926, 1559, 1364, 1026 and 916 cm−1 for the biochar samples). CO2 capture was performed by thermogravimetric running test. The samples showed similar physico-chemical characteristics, but the CA-2 sample showed better adsorption performance (1.22 mmol CO2 g−1). Heat treatment in an inert atmosphere and chemical activation of biomass are recommended for obtaining carbonaceous material for use in carbon dioxide adsorption processes.
Keywords: Carbonaceous material; CO2 capture; TG/DTG; Thermochemical activation